The specificity of training prescription and physiological assessment: A review - Reilly, T.; Morris, T.; Whyte, G. (Journal of Sports Sciences, 2009)
The aims in this review are: (1) to identify physiological determinants of performance; (2) to consider training specificity by examining aerobic, team and racket sports, strength and power activities, and cross-training and concurrent training methods; and (3) to evaluate the role of specificity in the physiological assessment of performance determinants. Assessment of the physiological determinants of performance is an integral part of sports science support for elite athletes. Laboratory and field-based physiological assessments are fundamental elements in profiling athletes, assessing training adaptations, and interrogating programme efficacy. The relatively small and highly specific adaptations associated with high-performance training call for valid, reliable, and sensitive methods of assessment. Recent advances in the physiological assessment of athletes have led to the development of a plethora of laboratory and field-based procedures. In the assessment of the athlete, there is a tension between the high reliability and low ecological validity of laboratory assessments and the low reliability and high validity of field-based methods. In an attempt to enhance ecological validity of training and physiological assessment, various sports-specific ergometers have been designed. This development has helped to match fitness assessment procedures to the demands of the sport concerned.